2014
DOI: 10.1371/journal.pone.0103587
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia Preconditioned Mesenchymal Stem Cells Prevent Cardiac Fibroblast Activation and Collagen Production via Leptin

Abstract: AimsActivation of cardiac fibroblasts into myofibroblasts constitutes a key step in cardiac remodeling after myocardial infarction (MI), due to interstitial fibrosis. Mesenchymal stem cells (MSCs) have been shown to improve post-MI remodeling an effect that is enhanced by hypoxia preconditioning (HPC). Leptin has been shown to promote cardiac fibrosis. The expression of leptin is significantly increased in MSCs after HPC but it is unknown whether leptin contributes to MSC therapy or the fibrosis process. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…In some reports, TPM isoforms have also been observed on the outside of cells, and cell culture experiments have demonstrated the presence of TPM on the surface of various cells that were derived from the colon, including primary cultures of colonic epithelial cells [33]. Our studies suggest that TPM1 and TPM2 are probably located in extracellular vesicles that are derived from multiple cell and tissue types [34][35][36][37]. These proteins are not generally known as secreted molecules of MSCs, but they could be released via the secretion of extracellular vesicles or exosomes in response to hypoxia.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In some reports, TPM isoforms have also been observed on the outside of cells, and cell culture experiments have demonstrated the presence of TPM on the surface of various cells that were derived from the colon, including primary cultures of colonic epithelial cells [33]. Our studies suggest that TPM1 and TPM2 are probably located in extracellular vesicles that are derived from multiple cell and tissue types [34][35][36][37]. These proteins are not generally known as secreted molecules of MSCs, but they could be released via the secretion of extracellular vesicles or exosomes in response to hypoxia.…”
Section: Discussionsupporting
confidence: 57%
“…A recent study demonstrated that the activation of cardiac fibroblasts was inhibited in leptin-deficient MSCs exposed to hypoxia [34]. The authors found that co-cultured MSCs showed decreased fibroblast activation and that preconditioning the cells with hypoxia enhanced these effects.…”
Section: Discussionmentioning
confidence: 98%
“…Interleukins may act to inhibit cardiac fibroblast proliferation and collagen production as well as myofibroblast differentiation, 171 while MSC-derived leptin was shown to inhibit fibroblast activation by blocking pathways involving TGFβ/‘small mothers against decapentaplegic’ (Smad) and Myocardin-Related Transcription Factor-A. 172 …”
Section: Fibroblasts and Adult Myocardial Homeostasismentioning
confidence: 99%
“…9 On the other hand, Chen et al has shown that leptin has an inhibitory effect on fibroblast activation. 20 This differential effect of adipokines on VSMC and AF could explain our in vitro findings; VSMC and AF proliferation responded differently to adipocyte-conditioned media. However, in vivo there is a more complex interplay, and adipose-derived leptin has an overall effect that promotes neointimal hyperplasia.…”
Section: Discussionmentioning
confidence: 59%